Bile Acids Repress Hypoxia-Inducible Factor 1 Signaling and Modulate the Airway Immune Response - Legendre, C.; Reen, F.; Woods, D.; Mooij, M.; Adams, C.; O'Gara, Fergal (American Society for Microbiology, 2014)
Gastroesophageal reflux (GER) frequently occurs in patients with respiratory disease and is particularly prevalent in patients with cystic fibrosis. GER is a condition in which the duodenogastric contents of the stomach leak into the esophagus, in many cases resulting in aspiration into the respiratory tract. As such, the presence of GER-derived bile acids (BAs) has been confirmed in the bronchoalveolar lavage fluid and sputum of affected patients. We have recently shown that bile causes cystic fibrosis-associated bacterial pathogens to adopt a chronic lifestyle and may constitute a major host trigger underlying respiratory infection. The current study shows that BAs elicit a specific response in humans in which they repress hypoxia-inducible factor 1α (HIF-1α) protein, an emerging master regulator in response to infection and inflammation. HIF-1α repression was shown to occur through the 26S proteasome machinery via the prolyl hydroxylase domain (PHD) pathway. Further analysis of the downstream inflammatory response showed that HIF-1α repression by BAs can significantly modulate the immune response of airway epithelial cells, correlating with a decrease in interleukin-8 (IL-8) production, while IL-6 production was strongly increased. Importantly, the effects of BAs on cytokine production can also be more dominant than the bacterium-mediated effects. However, the effect of BAs on cytokine levels cannot be fully explained by their ability to repress HIF-1α, which is not surprising, given the complexity of the immune regulatory network. The suppression of HIF-1 signaling by bile acids may have a significant influence on the progression and outcome of respiratory disease, and the molecular mechanism underpinning this response warrants further investigation.